2018
DOI: 10.1002/hed.25080
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymph node ratio in head and neck squamous cell carcinoma

Abstract: The LNR is reported to be of value in assessing prognosis in the patients with HNSCC. Although it is easy to calculate and could be considered in the staging of these patients, the currently available evidence in the literature does not yet provide a solid base for implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 35 publications
3
63
1
Order By: Relevance
“… 28 Tumor invasion and TNM stage are vital factors for assessment of prognosis in patients with cancer and are among the most common tools used for that purpose. 29 31 Our analyses revealed that DKK1 expression was higher in HNSCC patients with advanced tumor and clinical stage compared with those with early-stage disease, supporting a possible role for DKK1 in the development of HNSCC.…”
Section: Discussionmentioning
confidence: 60%
“… 28 Tumor invasion and TNM stage are vital factors for assessment of prognosis in patients with cancer and are among the most common tools used for that purpose. 29 31 Our analyses revealed that DKK1 expression was higher in HNSCC patients with advanced tumor and clinical stage compared with those with early-stage disease, supporting a possible role for DKK1 in the development of HNSCC.…”
Section: Discussionmentioning
confidence: 60%
“…Human head and neck squamous cell carcinomas (SCC) typically reveal a phenotype of collective cell movement [14]. Indeed, clustered cohort-like cancer cell dissemination appears to be highly efficient in embolizing lymphatic and blood vessels, which are accepted as a major prognostic factor for head and neck SCC [15]. Nevertheless, little is known about the complexity of collective cell invasion in this cancer type and further work is required in order to fully understand the involvement of phenotypic plasticity of tumor and stromal cells in this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a lower LNR may signify that few lymph nodes are positive out of the total removed and in consequence, the lower the value the higher the survival rate should be. Various potentially optimal cut-off values of LNY and LNR have been proposed in many retrospective studies and in two published systematic reviews [ 2 , 3 ], although no definitive results have been drawn yet. Elective neck dissection for cN0 oral and oropharyngeal cancer is routinely performed in many centers, considering the risk of occult metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…LNY and LNR may have a predictive value which may help to drive treatment choices in specific population of patients. The majority of the evidence on this topic comes from retrospective studies or cancer database registries [ 3 ], which are undoubtedly a valid source of information but are also predisposed to biases due to the retrospective collection of information, such as patient selection and incomplete data acquisition. For this reason, a routine evaluation of the two parameters is not part of current clinical practice.…”
Section: Introductionmentioning
confidence: 99%